Domestic Market Integration and the Law of One Price in Brazil - Goes, Carlos; Matheson, Troy. (Washington, D.C. : International Monetary Fund, 2015)
This paper presents the first assessment domestic market integration in Brazil using the law of one price. The law of one price is tested using two panel unit root methodologies and a unique data set comprising price indices for 51 products across 11 metro-areas. We find that the law of one price holds for most tradable products and, not surprisingly, non-tradable products are found to be less likely to satisfy the law of one price. While these findings are consistent with evidence found for other countries, price convergence occurs very slowly in Brazil, suggesting relatively limited domestic market integration.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Domestic Market Integration; Law Of One Price; Null Hypothesis; Panel Cointegration; WP; Brazil